2014
DOI: 10.1093/jjco/hyu116
|View full text |Cite
|
Sign up to set email alerts
|

Using Drawing Tests to Explore the Multidimensional Psychological Aspects of Children with Cancer

Abstract: In seeking to understand how life-threatening illness affects children psychologically, projective testing may be beneficial, particularly when attempting to identify psychological problems in younger adolescents. The advantages of projective testing are that it does not depend on patients' verbal ability and is not invasive. Three cancer inpatients from Kyoto Prefectural University of Medicine, aged between 10 and 16 years old, participated in the study. Projective testing was used to measure the depth of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Various studies have determined that adolescents receiving cancer treatment experience depression and high levels of anxiety due to factors such as cancer-related discomforts and physical symptoms (Allen et al, 1997;Hatano et al, 2014). In our study, the anxiety and depression scores of adolescents in the intervention group decreased significantly after the two sessions of mandala drawing compared to the control group.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Various studies have determined that adolescents receiving cancer treatment experience depression and high levels of anxiety due to factors such as cancer-related discomforts and physical symptoms (Allen et al, 1997;Hatano et al, 2014). In our study, the anxiety and depression scores of adolescents in the intervention group decreased significantly after the two sessions of mandala drawing compared to the control group.…”
Section: Discussionmentioning
confidence: 44%
“…Recently, nurses working in paediatric oncology centres have offered a number of psychosocial care services. However, paediatric oncology patients may experience psychological symptoms and inadequate coping (Hatano et al, 2014;Wiener et al, 2015). As it is understood from the literature, nurses need to transfer different psychosocial care approaches such as art therapy to their routine clinical practices.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy is designed to allow the child to respond openly to an ambiguous stimulus to reveal internal conflicts and subconscious distress. 17 Drawing can be used in any setting and for many purposes, such as diagnosis, assessment, research, or the measurement of progress in therapy. It is used as an art therapy and represents a phenomenological approach.…”
Section: Discussionmentioning
confidence: 99%
“…Drawings made by patients have been successfully applied in a number of medical conditions and report that patients find it easier to illustrate their feelings more accurately by a drawing than they can express them with words . Previous studies on patients’ drawings in which drawing characteristics were scored were identified by a PubMed search (March 20, 2015) and resulted in 18 studies (Table ) . These studies demonstrate that drawings made by patients reveal their perceptions on their illness.…”
Section: Introductionmentioning
confidence: 99%